Magnitude and Associated Factors of Unintended Pregnancy among Pregnant Women at Saesie Tsaeda Emba Woreda Eastern Zone of Tigray, North Ethiopia, 2018 - Gebrehiwot Gebremariam Weldearegawi; Kidanemaryam Berhe Tekola; Berhane Fseha Teklehaymanot (Journal of Pregnancy)
Background. Each year there were about 80 million women who experienced unintended pregnancy in the globe. In Ethiopia, around one third of women have experiences of unintended pregnancy. However, the magnitude of unintended pregnancy was not determined in the study area. Hence the aim of the study was to assess the magnitude and associated factors of unintended pregnancy among pregnant women. Methods. Institutional based cross-sectional study design was employed among 345 participants. Participants were selected by systematic random sampling. Data was collected though face to face interview by structured questioner. It was entered, clean and analyzed using SPSS version 20. Descriptive analysis was done to see the frequency, percentage, mean and standard deviation. Adjusted odds ratio was computed at 95% confidence level to determine the effect of independent variable on the outcome variable. Variable at p value < 0.05 was declared as statistically significant variable. Model goodness of fit was checked using Hosmer lemeshow test. Result. The overall magnitude of unintended pregnancy was 24.9%. Employed women were 60% less likely having unintended pregnancy (AOR 0.4, 95% CI: 0.015, 0.785).Single women were 1.4 times more likely reported unintended pregnancy (AOR 1.4, 95% CI: 1.005, 3.675). Unintended pregnancy among ever visited by health extension workers was 1.7 times higher than not visited (AOR 1.7, 95% CI: 1.09, 5. 128). Unintended pregnancy among who had information about family planning were about 70% less likely reported unintended pregnancy than their counterparties (AOR 0.3, 95% CI: 0 .067, 0.845). Marital status, occupational status, visited by health extension workers, having information about family planning, discussing with their partners about contraceptive were found the major factors of unintended pregnancy. Thus the district health office, Tigray regional health office and other stakeholder should work to improve family planning accessibility, awareness, and utilization to overcome the problem.